The measure [large type] : a novel - Erlick, Nikki (Harper Large Print, an imprint of HarperCollins Publishers, 2022)
It seems like any other day: You wake up, pour a cup of coffee, and head out. But today when you open your front door, waiting for you is a small wooden box. This box holds your fate inside: the answer to the exact number of years you will live. From suburban doorsteps to desert tents, every person on every continent receives the same box. In an instant, the world is thrust into a collective frenzy. Where did these boxes come from? What do they mean? Is there truth to what they promise? As society comes together and pulls apart, everyone faces the same shocking choice: Do they wish to know how long they'll live? And, if so, what will they do with that knowledge? The Measure charts the dawn of this new world through an unforgettable cast of characters whose decisions and fates interweave with one another: best friends whose dreams are forever entwined; pen pals finding refuge in the unknown; a couple who thought they didn't have to rush; a doctor who cannot save himself; and a politician whose box becomes the powder keg that ultimately changes everything.